Photodynamic therapy and subthreshold micropulse laser treatment – A novel combined approach for the treatment of serous retinal detachment in dome-shaped macula - Pirani, Vittorio; Pelliccioni, Paolo; Giovannini, Alfonso; Nicolai, Michele; Cesari, Claudia; Mariotti, Cesare (Photodiagnosis and photodynamic therapy, 2020)
•Serous retinal detachment is a common complication of dome-shaped macula (DSM).•There is no validated therapy leading to serous retinal detachment resolution in DSM.•A combined new treatment, using PDT and micropulse laser treatment, is reported.•Half-fluence half-dose PDT reduces the risk of chorioretinal atrophy.•Visual and anatomical outcomes of a safe and effective combined therapy are reported. Dome-shaped macula (DSM) is characterized by an inward convexity of the macula in myopic eyes, as visualized on optical coherence tomography (OCT). Serous retinal detachment (SRD) is a common complication of DSM, leading to a deterioration of visual acuity, in association with retinal pigment epithelium (RPE) atrophic changes. Many different therapeutic approaches to SRD secondary to DSM have been attempted, with variable results. We report our experience (11 treatment-naïve patients) with a combined new treatment approach, using half-fluence and half-dose photodynamic therapy (PDT) followed by subthreshold 577 nm micropulse laser treatment (STLT), for SRD related to DSM after a 6-month follow-up. Central foveal thickness was significantly decreased at the end of the follow-up. SRD diminished in all cases, and 5 eyes (45.4 %) registered complete resolution at the end of the 6-month follow-up, while 6 eyes (54.5 %) experienced two lines of improvement in BCVA at the end of the follow-up. No case showed postoperative complications. Therefore, this represents the first study evaluating the visual and anatomical outcomes of a safe and effective combined treatment of SRD in DSM.